MADRASA OF MUSTAFA PASHA AL-NASHAĀR IN ZABĪD, YEMEN; ARCHITECTURAL AND ARCHEOLOGICAL STUDY - Mohamed Enab (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
Madrasa of Mustafa Pasha Al-Nashaār is considered one of the most prominent buildings of Ottoman architecture in Yemen. It has commissioned by Mustafa Pasha al-Nashaār, the first Ottoman governor of Yemen, in 962-963AH/1554 AD. The Madrasa is built on the south side of Zabīd to spread the Hanafite and Shafite Sunni doctrines, replacing and eliminating the Zaydi Shiite doctrine. It contains a mausoleum dome for Mustafa Pasha Al- Nashaār and his family. The Madrasa's apparent Ottoman style is displayed through a main domed section and a multiple-domed portico. In this paper, the researcher provides a short biography of Mustafa Pasha Al-Nashaār, a descriptive and analytical study of The Madrasa and its distinctive architectural and artistic features. The paper sheds some new insights on the history of The Madrasa regarding its historical importance and distinctive architectural style as an excellent example of the Ottoman style in Yemen. The paper also aims to raise concerns about its exposure to demolition threats and ruin due to Yemen's current war and conflict.